2021
DOI: 10.3390/ijerph18126476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodic Vehicle Inspection on Road Crashes and Injuries: A Systematic Review

Abstract: This systematic review was conducted to determine the effect of periodic motor vehicle inspections on road crashes and injuries, compared to less exposure to periodic inspections or no inspections. The Medline, Web of Science, and Scopus databases were used to search the literature. Ecological studies were specifically excluded. A reverse search of the results with these databases and of other identified narrative reviews was also performed. Of the 5065 unique references initially extracted, only six of them m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the study by [24], a systematic review was performed to determine the effect of VTIs on road crashes and injuries and experiences with fewer or non-periodic inspections were compared. The authors suggest that periodic inspection is associated with a slight decrease in road crashes and they outline the need to conduct further studies that provide conclusive scientific evidence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study by [24], a systematic review was performed to determine the effect of VTIs on road crashes and injuries and experiences with fewer or non-periodic inspections were compared. The authors suggest that periodic inspection is associated with a slight decrease in road crashes and they outline the need to conduct further studies that provide conclusive scientific evidence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The conclusions of these studies and research are generally divided. A first group of researchers [12][13][14][15][16][17][18][19][20][21][22][23][24] came to the conclusion that TIV has an impact on the state of traffic safety. Another group of researchers [25][26][27] came to the conclusion that TIV has no impact on the occurrence of traffic accidents and the state of traffic safety.…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…Martín-delosReyes et al [6] reviewed the existing literature on the effect of vehicle roadworthiness inspections in road accidents. They highlighted the wide variety of results; nevertheless, it was concluded that periodic vehicle inspections are associated with a slight reduction in road accidents.…”
Section: Introductionmentioning
confidence: 99%